2001
DOI: 10.1016/s1010-7940(01)00674-1
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic disease after heart transplantation: single center experience

Abstract: Cancer is a strong limitation for long-term survival after heart transplantation. The only risk factor recognized is the patient's age at the time of transplant. Furthermore, the type of prophylactic globulins used for induction therapy and some specific immunosuppressant agent (azathioprine) may play a significant role in the development of malignancies after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 12 publications
4
44
0
6
Order By: Relevance
“…7 ). In our study it was not possible to calculate adjusted risk for different types of NMSC, as data in the external group do not specify the exact type of NMSC.The relatively low incidence of skin cancer in a cohort of HTRs was recorded by Rinaldiet al or Park et al in a single centre in Korea 8,9 . Unlike most studies reported, the authors found significantly higher incidence of lung cancer (39%) and non-Hodgkin lymphomas (20%).…”
Section: Discussionmentioning
confidence: 86%
“…7 ). In our study it was not possible to calculate adjusted risk for different types of NMSC, as data in the external group do not specify the exact type of NMSC.The relatively low incidence of skin cancer in a cohort of HTRs was recorded by Rinaldiet al or Park et al in a single centre in Korea 8,9 . Unlike most studies reported, the authors found significantly higher incidence of lung cancer (39%) and non-Hodgkin lymphomas (20%).…”
Section: Discussionmentioning
confidence: 86%
“…The incidence of solid tumors is relatively low, and pancreatic cancer is particularly rare in HTx patients. 2) We have described here a case of pancreatic cancer that emerged 4 years and 8 months after HTx. The cancer was recognized by abnormalities in hepato-biliary enzymes due to biliary stricture and elevation of CA19-9.…”
Section: Discussionmentioning
confidence: 96%
“…1) Most malignancy emerges in skin or in the form of lymphoproliferative disorder, but pancreatic cancer has been infrequently reported in HTx patients. 2) To the best of our knowledge, there have been no reports on chemotherapy for pancreatic cancer in HTx patients.…”
mentioning
confidence: 99%
“…Indications for heart transplant Rinaldi and associates 13 and Goldstein and associates 14 have both presented considerable data regarding neoplastic diseases in cardiac transplant patients. In light of their studies, cardiomyopathy was identified as the single most important pathology leading to cardiac transplant.…”
Section: Introductionmentioning
confidence: 99%
“…13 Different types of drugs are used for immunosuppressive therapy in heart transplant patients, each with a different role during treatment. As reported by Rinaldi and associates, 13 the intensity of immunosuppression used to prevent and treat rejection is directly proportional to the adverse effects and posttransplant malignancies.…”
Section: Introductionmentioning
confidence: 99%